Information aggregation problem of 4 tuple linguistic based on hedge algebra - Long, Nguyễn Văn; Thông, Hoàng Văn (Journal of Computer Science and Cybernetics, 2012)
The role of information aggregation problems is in general very important in the decision process and hence they can find applications in many fields, particularly, for the fuzzy information aggregation problem since human makes decisions by means of vague linguistic terms. So far there are many methods have been exploited to solve these problems but mainly based on fuzzy sets. The works [8] and [7] were devpted to solve this problem, applying hedge-algebra-based semantics of linguistic terms to representing linguistic data by 2-tuples or 3-tuples. In this paper we introduce 4-tuple representation exploiting more deeply hedge-algebra-based semantics of linguistic terms for solving this problem. This allows represent the semantics of linguistic symbols in rating scale more completely and hence it produces output results more exactly and naturaly.